Design of functionalized α-Fe2O3 (III) films with long-term anti-wetting properties. Issue 5 (1st April 2020) - Liang, Taotao; Guo, Xiaogang; Yuan, Binfang; Kong, Shuying; Huang, Huisheng; Fu, Daoling; Zhang, Fulan; Xu, Jianhua; Li, Xueming
Abstract: The design of functional anti-wetting ceramic coatings is always a bottleneck restricting the development of ceramic techniques. This study proposes a liquid phase synthesis method to fabricate α-Fe2 O3 (III) ceramic powders with promising applications and introduces a facile electrophoretic deposition (EPD) technique to construct the corresponding functionalized hydrophobic films – superhydrophobic functionalized α-Fe2 O3 ceramic films (SFOFS) with roughly even distribution and a high water contact angle (CA) of 169°±1° – followed by heat posttreatments. The microtopography and crystalline structures of the product were investigated by FESEM, EDX, and XRD techniques. The EPD controllability of SFOFS was studied by adjusting the EPD time and the applied field strengths. In addition, the SFOFS show excellent long-term anti-wetting properties for twenty-four months after undergoing a series of tests, including soaking, water droplet impacting, immersion by droplets with different surface tensions and exposure to different gases and relative humidity conditions, etc. This study substantially helps the design of other kinds of functional anti-wetting films through the proposed convenient method beyond the oxide limit. Graphical abstract: Image 1